Neutrophil extracellular traps in feline cardiogenic arterial thrombi: a pilot study. Issue 6 (June 2022) - Li, Ronald HL; Nguyen, Nghi; Stern, Joshua A; Duler, Laetitia M
Objectives: The aim of this study was to investigate the spatial distribution of neutrophil extracellular traps (NETs) in cardiogenic arterial thromboembolism (CATE). Specifically, we aimed to examine the related structural features of NETs in feline arterial thrombi in relation to their arterial locations. Methods: Paraffin-embedded aortic bifurcations from nine cats with hypertrophic cardiomyopathy (four with CATE and five without) were deparaffinized, and NETs were identified by immunodetection based on colocalization of cell-free DNA, citrullinated histone H3 and neutrophil elastase. The distribution of NETs in thrombi within the aortic bifurcations and common iliac arteries (CIAs) was compared based on their proximity to the descending aorta (proximal, mid, distal). Ten random fields per section were captured at × 10 and × 20 magnification for each section of the clot and analyzed. Results: The distributions of NETs in thrombi within the aortic bifurcation and CIAs were found to differ in relation to their assigned zones (proximal, mid, distal; P = 0.04); NETs were concentrated mostly in the proximal region in the aortic bifurcations (47.56%, interquartile range [IQR] 14.07–77.95) and CIAs (44.69%, IQR 24.65–85.28), compared with the distal regions (2.69%, IQR 0.10–50.04 [P = 0.027]; 7.08%, IQR 1.27–59.33 [P = 0.02]). Conclusions and relevance: The variation in NET distribution within arterial thrombi may shed light on the pathogenesis of thrombus growth. This may be due to possible neutrophil entrapment or variations in shear stress.